(untitled) (Journal of the Society for Musicology in Ireland, 2025)
A review of Peadar Ó Riada, Ceoltóirí Chualann: The Band that Changed the Course of Irish Music (Cork: Mercier Press, 2024), ISBN 9781781178690, 256pp., €24.99 (hardback).